History of Criminal Law Enforcement and Islamic Justice in Saudi Arabia - Casduloh (Penerbit Hellow Pustaka, 2023)
The Saudi Arabian judiciary can be an option for a modern justice system and is interesting to study because of several things, the first of which is that Saudi Arabia is the birthplace of the Prophet Muhammad SAW. and the Islamic religion is a role model for people throughout the world, but this country has a different government system from other Muslim countries. Saudi Arabian law is based on sharia which consists of the Koran and Sunnah. Ijmak and qiyas which were developed by the ulama after the death of the Prophet Muhammad also became sources of law. Judges' decisions in Saudi Arabia are heavily influenced by the writings of the Hanbali school of thought. Saudi Arabia is the only country in the world that makes the Koran and Sunnah its constitution, or at least it does not conflict with Islamic sharia and nothing else. The judiciary in Saudi Arabia is divided into three levels, namely Immediate Justice (al-mahakim al-musta'jilah) , Syar'iyah Court (al-mahakim asy-syar'iyyah) and the Judicial Supervisory Body (Hay'ah al-Muraqabah al- Qadha'iyyah).